2013
DOI: 10.1111/bjh.12301
|View full text |Cite
|
Sign up to set email alerts
|

Does BCR/ABL1 positive Acute Myeloid Leukaemia Exist?

Abstract: Summary The BCR/ABL1 fusion gene, usually carried by the Philadelphia chromosome (Ph) resulting from t(9;22)(q34;q11) or variants, is pathognomonic for chronic myeloid leukaemia (CML). It is also occasionally found in acute lymphoblastic leukaemia (ALL) mostly in adults and rarely in de novo acute myeloid leukaemia (AML). Array Comparative Genomic Hybridization (aCGH) was used to study six Ph(+)AML, three bi‐lineage and four Ph(+)ALL searching for specific genomic profiles. Surprisingly, loss of the IKZF1 and/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 24 publications
2
68
0
1
Order By: Relevance
“…Preliminary data suggest that deletion of antigen receptor genes (IGH, TCR), IKZF1 and/or CDKN2A may support a diagnosis of de novo disease vs BP of CML. 80 Although the WHO authors struggled with how to incorporate the recent discoveries in gene mutations in AML, [81][82][83] the text for all disease categories is expanded to discuss the prognostic significance of various gene mutations and their frequency in the different AML subtypes. An updated table further summarizes the various genes mutated in AML and their significance (supplemental Table 2).…”
Section: Acute Myeloid Leukemia Aml With Recurrent Genetic Abnormalitiesmentioning
confidence: 99%
“…Preliminary data suggest that deletion of antigen receptor genes (IGH, TCR), IKZF1 and/or CDKN2A may support a diagnosis of de novo disease vs BP of CML. 80 Although the WHO authors struggled with how to incorporate the recent discoveries in gene mutations in AML, [81][82][83] the text for all disease categories is expanded to discuss the prognostic significance of various gene mutations and their frequency in the different AML subtypes. An updated table further summarizes the various genes mutated in AML and their significance (supplemental Table 2).…”
Section: Acute Myeloid Leukemia Aml With Recurrent Genetic Abnormalitiesmentioning
confidence: 99%
“…Distinction from blast phase of chronic myeloid leukemia may be difficult; preliminary data suggest that deletion of antigen receptor genes (immunoglobulin heavy chain and T-cell receptor), IKZF1, and/or CDKN2A may support a diagnosis of AML rather than chronic myeloid leukemia blast phase. 9 AML with mutated NPM1 and AML with biallelic mutations of CEBPA have become full entities; the latter category was restricted to cases with biallelic mutations because recent studies have shown that only those cases define the entity and portend a favorable outcome. [10][11][12][13][14][15][16] Both entities now subsume cases with multilineage dysplasia because presence of dysplasia lacks prognostic significance.…”
Section: Aml With Recurrent Genetic Abnormalitiesmentioning
confidence: 99%
“…The second challenge arose when the Fish result showed positive Philadelphia chromosome, the question was whether it is Blast crisis of CML or Denovo AML with positive ph chromosome. Preliminary data suggest that additional molecular markers such as deletion of antigen receptor genes (IGH, TCR), IKZF1 and/or CDKN2A may support a diagnosis of de novo ABL over blast crisis of CML [7]. Unfortunately those molecular markers are not available in our laboratory.…”
Section: Discussionmentioning
confidence: 95%